2014
DOI: 10.3109/03639045.2014.920024
|View full text |Cite
|
Sign up to set email alerts
|

Cryomilling-induced solid dispersion of poor glass forming/poorly water-soluble mefenamic acid with polyvinylpyrrolidone K12

Abstract: The effect of mechanical impact on the polymorphic transformation of mefenamic acid (MFA) and the formation of a solid dispersion of mefenamic acid, a poor glass forming/poorly-water soluble compound, with polyvinylpyrrolidone (PVP) K12 was investigated. The implication of solid dispersion formation on solubility enhancement of MFA, prepared by cryomilling, was investigated. Solid state characterization was conducted using powder X-ray diffraction (PXRD) and Fourier-transform infrared (FTIR) spectroscopy combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Ninety-two of the 101 studies reported solubility and dissolution studies (7174,7779,8192,95,97107,109111,113119,121,123,124,126133,135139,141154,156,157,160,161,166,168176). The USP in vitro dissolution type II apparatus was the most commonly used instrument (67%), followed by the USP type I apparatus (6%), while the remaining 27% used various other apparatuses, including modified versions of the USP type I only (148) or paired with confocal Raman microscopy (98), USP types I and II apparatus (72), USP type IV (152), closed loop of USP types II and IV (152), a perspex flow cell (73,142), a rotary mixer (131), a Chinese pharmacopoeia type III apparatus (118), an in-house miniaturized USP type II apparatus (175), Sirius T3 apparatus (146), μFLUX dissolution-permeation apparatus (141), Raman UV-Vis flow cell system (99), a centrifuge (88), high throughput screening using a 96-well plate (82,115,157), Wood’s apparatus (99,137), an orbital shaking incubator (156), and another shake-flask method (171) (Fig. 6).…”
Section: Current Status Of Research On Amorphous Formulationsmentioning
confidence: 99%
“…Ninety-two of the 101 studies reported solubility and dissolution studies (7174,7779,8192,95,97107,109111,113119,121,123,124,126133,135139,141154,156,157,160,161,166,168176). The USP in vitro dissolution type II apparatus was the most commonly used instrument (67%), followed by the USP type I apparatus (6%), while the remaining 27% used various other apparatuses, including modified versions of the USP type I only (148) or paired with confocal Raman microscopy (98), USP types I and II apparatus (72), USP type IV (152), closed loop of USP types II and IV (152), a perspex flow cell (73,142), a rotary mixer (131), a Chinese pharmacopoeia type III apparatus (118), an in-house miniaturized USP type II apparatus (175), Sirius T3 apparatus (146), μFLUX dissolution-permeation apparatus (141), Raman UV-Vis flow cell system (99), a centrifuge (88), high throughput screening using a 96-well plate (82,115,157), Wood’s apparatus (99,137), an orbital shaking incubator (156), and another shake-flask method (171) (Fig. 6).…”
Section: Current Status Of Research On Amorphous Formulationsmentioning
confidence: 99%
“…Various techniques have been used in the investigation of solid dispersions (SDs) of various weakly soluble drugs and other organic compounds (Moneghini et al, 2008, Aso et al, 2009, Moneghini et al, 2009, Menéndez et al, 2010, Maurya et al, 2010, Van Eardenbrugh and Taylor, 2010, Issa et al, 2013, Paudel et al, 2013, Li et al, 2014, Xiqiang et al, 2014, Fulop et al, 2015, Kang et al, 2015, Wang et al, 2015, Altamimi and Neau, 2016). Microwave technology has been investigated rarely in literature in order to enhance solubility, in vitro dissolution, therapeutic efficacy and in vivo bioavailability of such drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The MFA form I was used as received without recrystalized. The MFA form II were recrystalized from DMF as described by Kang et al (2015). The IR absorption bands (Fig.…”
Section: Characterization Of Mfa Form I and Mfa Form Iimentioning
confidence: 99%
“…Many approaches have been studied to enhance solubility and dissolution profile of MFA. The techniques such as solid dispersion with polyvinylpyrrolidone (Kang et al, 2015) or modified starch (Vikram, 2012), a complex with cyclodextrin (Hladon et al, 1999), and also a cocrystal formation (Fabian et al, 2011) have been tried. The progress of solid stage of MFA in various pharmaceutical dosage form was also hindered by polymorphic transformation of MFA along of the formulation process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation